الفعالية الذاتية في مهارة الاستماع باللغة العربية : دراسة لدى طلبة جامعة مارا للتكنولوجيا بسراواق - Zulkefly bin Ibrahim (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2012)
This study aims to investigate the level of Arabic listening self-efficacy in a sample of 87 students at the University of Technology Mara (UiTM) Sarawak. In this study, self-efficacy items adapted from previous studies, were designed as a tool for measurement. Reliability test reveals that the items exceeded the benchmark of a high degree of stability as the value of overall reliability coefficient, Cronbach alpha = .769. Inferential statistical analysis by SPSS shows that the students' Arabic listening self-efficacy was at the middle level (moderate). On the other hand, no significant difference was found between genders, as well as any relationship between academic achievement and self-efficacy. However, the researcher has found a significant difference in students' Arabic listening self-efficacy at different Arabic levels of study. Reasons leading to the above-mentioned results were also discussed.